Aging, labor turnover and firm performance - Pekka Ilmakunnas; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2007)
We study whether older workers are costly to firms. Our estimation equations are derived from a variant of the decomposition methods frequently used for measuring micro-level sources of industry productivity growth. By using comprehensive linked employeremployee data from the Finnish business sector, we study the productivity and wage effects, and hence the profitability effects, of hiring and separation of younger and older workers. The evidence shows that separations of older workers are profitable to firms, especially in the manufacturing ICT-industries. Robustness checks include the use of regional labor supply and other variables as instruments for the potential endogeneity of the labor flows.
Keywords: C43; J23; J24; J63; M51; 330; aging; productivity; wage; profits; hiring; separation; employer-employee data; Ältere Arbeitskräfte; Industrie; Arbeitsproduktivität; Lohnniveau; Personalplanung; Rentabilität; Finnland